2006
DOI: 10.1007/s10834-006-9034-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Income Differentials: Comparing Asians with Whites and Blacks

Abstract: Census 2000 data are used to examine the determinants of income level of six Asian groups as compared with whites, the majority group, and blacks, another minority group. Results of descriptive and multivariate analysis lend support to both human capital investment and structural barriers as explanation for income differentials among the various racial groups. All else equal, Asian Indians did not have significantly different income levels as compared with white, whereas Chinese, Filipinos, Korean and Vietname… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Additionally, two-fifths had less than a high school degree and a low level of English proficiency, while 36% of Chinese immigrants had a bachelor's degree or higher. These findings are consistent with the previous research (Sharpe and Abdel-Ghany 2006) regarding socioeconomic polarization of Asian immigrants.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, two-fifths had less than a high school degree and a low level of English proficiency, while 36% of Chinese immigrants had a bachelor's degree or higher. These findings are consistent with the previous research (Sharpe and Abdel-Ghany 2006) regarding socioeconomic polarization of Asian immigrants.…”
Section: Discussionsupporting
confidence: 93%
“…However, researchers have challenged the validity of the model minority label. With the 2000 Census data, Sharpe and Abdel-Ghany (2006) found that five ethnic Asian groups, including Asian Indians, Chinese, Filipinos, Korean, and Vietnamese, had less or no different household income compared to whites except the Japanese, controlling for structural variables such as education and household size.…”
Section: Socioeconomic Status Of Asian Americansmentioning
confidence: 99%
See 1 more Smart Citation
“…For Asians in the United States, the poverty rate in 2012 was 11.7 %, compared to 9.7 % for non-Hispanic Whites, 27.3 % for Blacks and 25.6 % for Hispanics (DeNavas-Walt et al 2013). One of the most comprehensive studies of the income of Asians in the United States is that conducted by Sharpe and Abdel-Ghany (2006). Their study was also unusual in that it included analyses of different subsets of the Asian population.…”
Section: Financial Statusmentioning
confidence: 99%
“…Although there is much research on minority groups in the US, the research on household finance has centered on Blacks. Sharpe and Abdel-Ghany (2006) pointed out that most of the research stemmed from the civil rights movement of the 1960s and the struggle of Blacks for equal rights. There is no similar body of research on Asian households.…”
Section: Introductionmentioning
confidence: 99%